VARIATIONS OF WATER TEMPERATURE IN THE NORTHERN SEA OF OKHOTSK (Izmenchivost Temperaturnykh Uslovii vod Severnoi Chasti Okhotskogo Morya) - Vinokurova,T. T. (1970)
The main objective of this study is to elucidate the causes of formation and migration of the stable food source--the zooplankton. Thus, it is possible to determine the distribution of commercial concentrations of herring within the given sea region. It is known that in the northern Sea of Okhotsk the formation of hydrological regime in the spring-summer is basically determined by atmospheric processes of the preceding winter and the intensity of the influx of the warm Pacific water into the Sea of Okhotsk. Accordingly, this discussion tried to determine the interrelationship between the intensity of atmospheric processes over the Sea of Okhotsk and the area occupied by the intermediate cold water layer with minimal temperatures -1.7 degrees and the underlying water layers (thermal conditions of a given year). (Author) Trans. of Tikhookeanskii Nauchno-Issledovatelskii Institut Rybnogo Khozyaistva i Okeanografii. Izvestiya (USSR) v59 p14-26 1965, by M. Slessers.